The Effectiveness of Occupational Health and Safety Practices in Public Technical Training Institutes - Sangay Tshewang; Sonam Wangmo (Journal of Innovation in Polytechnic Education)
The study aimed to evaluate the extent of occupation-related injuries and accidents, the use of Personal Protective Equipment (PPE), Occupational Health and Safety (OHS) training, and awareness and implementation of OHS policy among Technical Training Institutes (TTIs).